Prolonged Transfusion-Dependent Temozolomide-Induced Thrombocytopaenia in Glioblastoma: Risk Factors Remain Elusive. (1st October 2022) - Ismail, Nashwah; Patel, Karan; Colaco, Rovel; Borst, Gerben; Milanovic, Dusan; McBain, Catherine
Abstract: AIMS: Temozolomide-induced thrombocytopaenia is well-recognised; clinical-course varies widely. Aims: To identify risk factors for prolonged thrombocytopaenia; improve patient-care; inform trial design. METHOD: Glioblastoma (GBM) patients requiring platelet transfusion were identified. (Local policy: transfuse when plt count ≤ 30 x 10 9 /L). Inclusion criteria: First-line-standard-of-care temozolomide-chemo-radiotherapy (TMZ-CRT). Case-notes reviewed for demographics, blood-counts, radiotherapy and treatment parameters. Thrombocytopaenia grading: CTCAE V5. Date of onset measured from start of TMZ-CRT to date of platelets < 100 x 10 9 /L, and to date of first instance of ≥ grade 3 thrombocytopaenia. Thrombocytopaenia duration: time to platelet count recovery to ≥ 100x109/L. RESULTS: Between 2017-2021, 69 patients required platelet transfusion; 68/69 identified on routine monitoring. 49 patients were analysed (6:no CRT; 5:trial study drug; 7:≥ 2nd line treatment; 2:inadequate data). Median age: 59 (range 25-73); 61% female. First incidence of thrombocytopaenia during concurrent TMZ-CRT: 27/49 patients; during adjuvant TMZ in 22/49 (13/22 following 6-week-TMZ-CRT, 9/22 following 3-week-TMZ-CRT). In concurrent patients, median time to thrombocytopaenia: 33 days (range 23-38); median duration: 44 days (range 20-105; 5 not recovered); number of transfusions: 1-2:9 pts; 3-4:6pts; 5-7:3pts; 8-10:7pts; >10:2pts. Of 22 adjuvant patients transfused, 8/22 developed ≥G3 thrombocytopaenia post-cycle-2; 19/22 resolved after 1 or 2 transfusions. Thrombocyopaenia was associated with ≥G3 neutropaenia in 11% of patients requiring <5 transfusions vs 75% requiring ≥ 5. Comparison of < 5 vs ≥ 5 transfusion-patients did not identify differences in any demographic or treatment parameters. CONCLUSION: Risk factors for prolonged TMZ-induced thrombocytopenia vs swiftly-resolving thrombocytopaenia remain elusive. This needs to be reflected in consent processes and in design of clinical trials.